Estudo das alterações do ritmo vigília-sono, da temperatura corporal e da secreção de melatonina em pacientes com doença pulmonar obstrutiva crônica - Nunes, Deuzilane Muniz (2012)
Previously, circadian alterations in chronic obstructive pulmonary disease (COPD) have been insufficiently investigated. In this work, consisting of three studies, we evaluated the impairments in sleep-wake rhythm, the circadian variation of oral temperature, the nocturnal melatonin secretion and morning cortisol concentration in patients with stable COPD. Initially, 26 patients with moderate to very severe COPD (mean age ± SD = 66.9 ± 8.5 years) and 15 controls (age = 63.0 ± 10.7 years) were evaluated by actigraphy for 5-7 days. Dyspnea, lung function (spirometry), sleep quality (Pittsburgh Sleep Quality Index, PSQI) and daytime sleepiness (Epworth Sleepiness Scale, ESS) were measured. Individuals with COPD showed increased sleep latency (p = 0.003), mean nocturnal activity (p = 0.003), and wake after sleep onset (p = 0.003). Furthermore, they presented reduced total sleep time (TST, p = 0.024) and lower sleep efficiency (p = 0.001). In patients, severity of dyspnea was correlated with activity levels during sleep (r = 0.41, p = 0.04) and with TST (r = -0.46, p = 0.02). Subjective sleep quality was poorer in patients than controls (p = 0.043). In the second study, oral temperature was measured every two hours, from 4:00 a.m to 10:00 p.m, in 31 patients with moderate to very severe COPD (age = 66.3 ± 6.5 years) as well as in 19 controls (age = 63.6 ± 5.4 years). Dyspnea, sleep quality (PSQI), daytime sleepiness (ESS), depressive symptoms (Beck Depression Inventory, BDI-II), fatigue (Fatigue Severity Scale, FSS), chronotype (morningness-eveningness Questionnaire, MEQ) and risk of sleep apnea (Berlin Questionnaire) were evaluated. COPD patients showed worse PSQI global score (p<0.001), BDI-II (p = 0.02) and FSS (p <0.001). Mean temperature at 4:00 a.m and 6:00 a.m were higher in patients than in controls (p = 0.001 and p = 0.02, respectively). In the COPD group, the temperature at 6:00 a.m was correlated with the PSQI global score (p = 0.015). In the third study, 11 patients with moderate or severe COPD (age = 64.4 ± 8.8 years) were evaluated with polysomnography, dyspnea, pulmonary function and comorbidities (Charlson Comorbidity Index, CCI) and they had the cortisol levels measured in the morning at 6:00 a.m. The concentration of melatonin was measured at 6:00, 7:00, 8:00, 9:00, 10:00, 11:00 p.m and, 0:00, 2:00, 4:00 and 6:00 a.m in seven cases. It was observed prolongation of REM sleep latency (118.1 ± 86.3 min), lower sleep efficiency (82.9 ± 11.6%) and elevated arousal index (16.3 ± 8.5 / h). The curves of melatonin secretion showed great variability. On average, the peak of melatonin (82.28 ± 49.4 pg / ml) occurred at 10:00 p.m. Sleep efficiency was correlated with the concentration of melatonin at 8:00 p.m (p = 0.05) and 11:00 p.m (p = 0.04) and the TST with melatonin concentration at 10:00 p.m (p = 0.05). The cortisol concentration at 6:00 a.m (22.08 ± 5.8 mg /dl) were correlated inversely with the arousal index (p = 0.04). In conclusion, clinically stable COPD patients presented sleep alterations assessed by actigraphy, associated with the degree of dyspnea. The rhythm of oral temperature was altered in COPD, with higher temperatures in the early morning, and this may be related to sleep disturbances. The pattern of melatonin secretion in COPD is variable. Cortisol morning levels and melatonin concentration measured at 8:00, 10:00 and 11:00 p.m are associated with changes in the sleep pattern of these patients.